Expression of selected nuclear receptors in human epithelial ovarian cell line Caov3 exposed to bisphenol derivatives - Mlynarcikova Alzbeta Bujnakova; Macejova Dana; Scsukova Sona (Endocrine Regulations, 2023)
Objectives. Bisphenol A (BPA) is an indispensable industrial chemical. However, as a proven endocrine disruptor, it may be associated with several health disturbances, including the reproductive functions impairment and cancer. Due to the restriction of BPA usage, many bisphenol derivatives gradually substitute BPA. However, studies have reported adverse biological effects of BPA analogs, but the specific sites of their action remain largely unknown. Nuclear receptors (NRs) appear to play significant roles in various types of cancer. In addition, they are considered relevant targets of bisphenols. In the present study, we investigated the effects of BPA and its analogs bisphenol S (BPS), bisphenol F (BPF), and bisphenol AF (BPAF) on mRNA expression of selected NRs in the human ovarian epithelial cell line Caov3. The NRs examined included retinoic acid receptor α (RARA), retinoid X receptor α (RXRA), peroxisome proliferator activating receptor β/δ (PPARD), chicken ovalbumin upstream promoter-transcription factor 2 (COUPTFII), and nuclear receptor-related protein 1 (NURR1).